Analisis Kebijakan Full Day School Dalam Membina Akhlak Siswa di Era Merdeka Belajar - Ramandhani, Desti Meliana; Yusro, Wardi; Nugroho, Dwi; Setiawan, Farid (An-Nuha, 2023)
Technological advances have affected various sectors in the world. One of them is in the education sector. Various advances and conveniences that have been presented in this technological era have succeeded in developing the education system. However, technological advances also have a negative impact on students, namely the occurrence of moral degradation. One of the efforts made by the government in dealing with this problem is by implementing a full day school policy. This study aims to describe and analyze full day school policies in fostering student morals in the era of independent learning. This research uses qualitative methods, with descriptive methods and library research. The results of the study state that the full day school policy is able to maintain and foster student morals from various deviations that occur in the school environment and outside the school.